OCIMUM SANCTUM LINN. (HOLY BASIL): PHARMACOLOGY BEHIND ITS ANTI- CANCEROUS EFFECT - BABY JOSEPH; VRUNDHA M. NAIR (International Journal of Pharma and Bio Sciences, 2013)
Presently, researchers have been given remarkable attention to complementary and alternative medicine to deal with cancer treatment from medicinal plants mainly due to its fewer side effects and ease availability. Several scientific studies deep- rooted the anti- cancerous property of Ocimum sanctum Linn., a traditional medicinal plant commonly known as Tulsi. The chemopreventive and radiopreventive property of O. sanctum along with its anti- oxidant, anti- inflammatory and anti- stress property reside as a backbone for it anti- cancerous effect. It is demonstrated that the cornerstone behind this effect is the various phytochemical constituents such as eugenol, orientin, vicenin- 2, linolenic acid and ursolic acid. The present review is an effort to amalgamate the various scientific studies underlying the anti-cancerous effect of O. sanctum under one roof. In this review, the anti-cancerous activity of O. sanctum in numerous cancers such as lung, skin, oral, cervical, gastric, breast and prostate were comprehensively represented.